Analysis of Bilal Faranov’s Communication Style in Motivational Content on the Instagram Account @suaraberkelas - Nazwa Sri Mutia; Mareta Puri Rahastine; Anggie Ayu Astria Latuperissa (Takaza Innovatix Labs Ltd., 2026)
This research is motivated by the increasing use of Instagram as a medium for disseminating motivational content, the success of which is influenced by the communicator's communication style. This study aims to analyze Bilal Faranov's communication style in motivational content on the Instagram account @suaraberkelas based on Robert W. Norton's Communication Style Theory. The study uses a descriptive qualitative approach with a constructivist paradigm. The research population is all motivational content on Instagram Reels on the @suaraberkelas account, while the sample was purposively selected in the form of three content pieces featuring Bilal Faranov as the main communicator. The research instrument is the researcher supported by observation, documentation, literature study, and interviews with three informants as triangulation. Data analysis is carried out through data reduction, data presentation, interpretation based on Norton's theory, triangulation, and drawing conclusions. The results show that the characteristics of impression leaving, open, dramatic, precise, relaxed, friendly, attentive, and animated expressive appear consistently in the three content pieces, while the dominant characteristics are only clearly visible in the monologue content. In conclusion, Bilal Faranov's communication effectiveness is built through a persuasive, friendly, clear, and audience-oriented communication style so as to strengthen engagement and acceptance of motivational messages on Instagram